Effectiveness and safety of surgical glove compression therapy as a prophylactic method against nanoparticle albumin-bound-paclitaxel-induced peripheral neuropathy. (October 2019) - Tsuyuki, Shigeru; Yamagami, Kazuhiko; Yoshibayashi, Hiroshi; Sugie, Tomoharu; Mizuno, Yutaka; Tanaka, Satoru; Kato, Hironori; Okuno, Toshitaka; Ogura, Nobuko; Yamashiro, Hiroyasu; Takuwa, Haruko; Kikawa, Yuichiro; et al.
Abstract: Background: We have developed a surgical glove (SG)-compression therapy and reported that this method significantly reduced the overall occurrence of grade 2 or higher nanoparticle albumin-bound-paclitaxel (nab-PTX)-induced peripheral neuropathy (PN) from 76.1% to 21.4%. In this multicenter single-arm confirmatory study, we investigated the efficacy and safety of SG-compression therapy for the prevention of nab-PTX-induced PN, compared with the incidence of grade 2 or higher PN in published literature as controls. Patients and methods: Primary breast cancer patients who received 260 mg/m 2 of nab-PTX were eligible for this study. Patients wore two SGs (one size smaller than the tight-fitting size) in each hand for 90 min. PN was evaluated at each treatment cycle using the Common Terminology Criteria for Adverse Events (CTCAE) version 4.0 and the Patient Neurotoxicity Questionnaire (PNQ). The temperature of each fingertip was measured using thermography. Results: Between October 2016 and June 2017, 58 patients were evaluated. The incidence of CTCAE grade 2 or higher PN was as low as 13.8% following SG-compression therapy. A goodness-of-fit test proved that the overall incidence of 13.8% grade 2 or higher PN in this study was comparable to the hypothesis-predicted value (13%). No adverse events, including compression intolerance or skin disorders caused by use of SG, were observed. SG-compression therapy significantly reduced the temperature of each fingertip by 1.3°C-2.3 °C compared to pre-chemotherapy level. Conclusions: This study suggested the safety and efficacy of SG-compression therapy for the amelioration of CIPN. Clinical trial number: UMIN 000024836. Highlights: A multicenter single-arm confirmatory study in breast cancer patients. Evaluated efficacy and safety of surgical glove (SG) compression therapy for CIPN. Incidence of Grade 2 or higher CIPN was as low as 13.8% by SG compression therapy. There were no skin disorders and no intolerance of compression by using SGs. This result was consistent with the results of our phase 2 study.